Vitamin D: Testing and supplementation in adults. Issue 11 (November 2020) - MacRae, Clare; Pearson-Stuttard, Ben; Ralston, Stuart H
Vitamin D is essential for the maintenance of musculoskeletal health through the regulation of calcium and phosphate homeostasis. Severe prolonged deficiency of vitamin D can lead to rickets in children and osteomalacia in adults. Both conditions are now rare in the UK, except in high-risk groups such as those with malabsorption and reduced exposure to sunlight. A much more common situation is 'biochemical' vitamin D deficiency, where circulating 25(OH)D concentrations fall below pre-defined thresholds in the absence of osteomalacia or rickets, making vitamin D deficiency and insufficiency very common in the UK particularly during the winter months and early spring. Biochemical vitamin D deficiency has been associated with various non-skeletal disorders, but it seems likely that the low vitamin D levels in these situations are the result of the underlying condition, rather than the cause.